(untitled) (Papeles, 2025)
In this article we made a theoretical overhaul to think about neoliberalism and its implications for youth in general, and for popular youth in particular. We start from understanding that neoliberalism is a political project that transcends economic objectives. We grasped it as a cultural and subjectivation model that has consumption and individuality in its center. According this, we consider that youth are the ideal target of these mandates and who, in turn, suffer from increasingly structural material conditions that neoliberalism itself provides. This tension represents helplessness for young people, the impossibility of projecting themselves materially and symbolically at a collective level. Then, the main idea of this article is to claim the importance of the social link as a tool of political dispute and professional intervention in scenarios where, as our subjects of intervention, we are helpless.